Peran Kepemimpinan Transformasional dalam Peningkatan Mutu Pendidikan Berbasis Teknologi - Tataq Harjuna Piranggada; Mi'at Mi'at; Nur Kholis Usman; Muhammad Triyoso; Yuliani Yuliani; Khairul Efendi; Suhaimi Suhaimi; Muhammad Saleh (Universitas Negeri Malang, 2025)
Abstract: This research documents a best practice of technology-based instructional leadership implemented at SMP Indocement Tarjun to improve the quality of learning in the digital era. The study was motivated by the initial conditions of the school, where teaching practices were still dominated by conventional lecture methods, teachers and students had relatively low digital competencies, and the available Information and Communication Technology (ICT) facilities had not been utilized optimally in the learning process. These conditions highlighted the need for an effective leadership strategy capable of encouraging systematic and sustainable technology-based learning transformation within the school environment. The purpose of this study is to analyze the model of transformational instructional leadership implemented in the school and to examine its impact on improving the quality of learning and overall school performance. This study employed a qualitative case study approach to explore deeply the implementation of instructional leadership practices within the school context. Data were collected through in-depth interviews with the principal, teachers, and students, direct observations of classroom learning activities, and documentation analysis related to digital learning practices and school achievements. The collected data were analyzed using descriptive qualitative analysis through data reduction, data display, and conclusion drawing. The findings reveal that collaborative and transformational instructional leadership serves as the main driving force in the implementation of technology-based learning transformation. This leadership approach successfully fostered three major components: (1) technology integration in learning through the use of interactive media, educational videos, and optimization of computer laboratories; (2) the development of teachers’ digital competencies through training programs in digital media production, coding, and the use of artificial intelligence (AI); and (3) the strengthening of a collaborative school culture that encourages innovation and the sharing of best practices among teachers. The synergy among these components contributes to increased student engagement in learning and significant improvements in students’ academic and non-academic achievements at district and provincial levels Keywords: Digitalization; Educational Technology; Instructional Leadership; Transformational Abstrak: Penelitian ini mendokumentasikan praktik baik (best practice) kepemimpinan pembelajaran berbasis teknologi di SMP Indocement Tarjun dalam upaya meningkatkan mutu pembelajaran di era digital. Penelitian ini dilatarbelakangi oleh kondisi awal sekolah yang masih menghadapi beberapa tantangan, seperti dominasi metode pembelajaran konvensional berbasis ceramah, rendahnya kompetensi digital guru dan siswa, serta pemanfaatan fasilitas Teknologi Informasi dan Komunikasi (TIK) yang belum optimal dalam proses pembelajaran. Kondisi tersebut menunjukkan perlunya strategi kepemimpinan yang mampu mendorong transformasi pembelajaran berbasis teknologi secara sistematis dan berkelanjutan. Penelitian ini bertujuan untuk menganalisis model kepemimpinan transformasional yang diterapkan di sekolah serta mengkaji dampaknya terhadap peningkatan mutu pembelajaran dan kinerja sekolah secara keseluruhan. Penelitian menggunakan pendekatan kajian kasus kualitatif (qualitative case study) untuk menggali secara mendalam praktik kepemimpinan pembelajaran yang berlangsung di lingkungan sekolah. Data penelitian dikumpulkan melalui wawancara mendalam dengan kepala sekolah, guru, dan siswa, observasi langsung terhadap proses pembelajaran, serta analisis dokumentasi terkait kegiatan pembelajaran, media digital, dan prestasi sekolah. Data dianalisis secara deskriptif kualitatif melalui proses reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kepemimpinan pembelajaran yang kolaboratif dan transformasional menjadi pendorong utama dalam proses transformasi pembelajaran berbasis teknologi di sekolah. Kepemimpinan tersebut mendorong terbentuknya tiga komponen utama, yaitu: (1) integrasi teknologi dalam pembelajaran melalui penggunaan media interaktif, video pembelajaran, dan optimalisasi laboratorium komputer; (2) pengembangan kompetensi digital guru melalui pelatihan pembuatan media digital, coding, dan pemanfaatan kecerdasan buatan (AI); serta (3) penguatan budaya sekolah kolaboratif yang mendorong inovasi dan berbagi praktik baik antar guru. Sinergi antara ketiga komponen tersebut terbukti berkontribusi pada peningkatan keterlibatan siswa dalam pembelajaran serta peningkatan prestasi akademik dan nonakademik siswa di tingkat kabupaten dan provinsi. Kata kunci: Kepemimpinan Pembelajaran; Transformasional; Teknologi Pendidikan; Digitalisasi